Apropriação da língua portuguesa escrita pelo surdo : um estudo de caso no CEAADA-MT - Härter, Larissa Ruth Siniak dos Anjos (2021)
This dissertation intends to understand the process of appropriation of Portuguese Language (LP) written as a second language (L2) by deaf students enrolled in the eighth year of Elementary Education at CEAADA (State Center for Assistance and Support to the Hearing Impaired), in Cuiabá. To this end, it aims to analyze sets of activities written from four textual genres, in an attempt to better understand the process of appropriation of L2 writing by this target audience. It was assumed by hypothesis, through studies already carried out, that there is an intrinsic relationship between sign language (LS) and the learning of L2; that access to LS as a mother tongue or first language since childhood, facilitates the cognitive development that will accompany the deaf student for life and will facilitate the learning of L2; and that there is a need to implement bilingual education and a suitable curriculum for teaching Portuguese as an L2 to the deaf. The research was Exploratory-Descriptive, through monitoring and participation in classes taught by LP for eight deaf apprentices enrolled in the eighth year of Elementary Education at CEAADA, whose ages vary between 14 and 16 years, constituting a qualitative research of the case study type and action research. For these subjects, four LP activities were proposed in partnership between the researcher and the conducting teacher in 2019. The analysis of productions written by these subjects, based on textual production in different textual genres, revealed that these learners are capable of appropriating written LP without the use of orality, however, they face some difficulties, among them, we can list: the appropriation of grammatical categories of LP; appropriation of punctuation marks from LP writing; appropriation of the phrasal structure of LP; appropriation of structures of textual types and textual genres and; appropriation of time and verbal mode for narratives. At the end of the analyzes, it was possible to ascertain that all the research subjects are in certain stages of interlingua - a term coined by Selinker (1972) to refer to the linguistic system used by a nonnative speaker who presents traces of the mother tongue - and are moving towards achieving the appropriation of the target language.This time, it was possible to place each subject in stages of writing appropriation, inspired by Brochado (2003) and adapted to our context. In summary, this dissertation intends to contribute so that literacy practices aimed at the deaf community are intensified in such a way as to assist in the appropriation of Portuguese writing, such as bilingual education. This effort will help this community to be an active participant in the community that surrounds it, in which literate practices assume a decisive role in the success of children and adolescents. Still, evaluating the appropriation of writing among the subjects of the eighth year at CEAADA provides a sample of the broad process of appropriation of LP writing by the deaf community, which allows to outline short, medium and long term pedagogical strategies for these subjects.